The Adaptation of Essential Material in Digital Natives Characteristics-based Sociology Subject in Senior High Schools - Siregar, Riadi Syafutra; Parahita, Bagas Narendra; Ghufronuddin; Dwi Astutik; Siany Indria Liestyasari; Atik Catur Budiati (Journal of Education Reseach and Evaluation, 2024)
The essential material is needed in Sociology learning to give the students an effective learning experience particularly in digitalization era. The suitability of essential material provided based on digital natives character increases social concern and interacting ability among the people. This research aims to analyze the appropriate essential material in Sociology learning subject matter needed by digital natives and teacher’s strategy in implementing. Qualitative research using observation and in-depth interview with 8 Sociology teachers as the technique collecting data is the research method used in this research. Data analysis was also used including the following stages: data collection, data reduction, data display, verification and conclusion drawing. The findings of research based urgency (U), relevance (R) and function (F) reveal essential material for digital natives consisting of social interaction and social dynamic, deviating behavior, social conflict, social change, local wisdom, and social research. Teachers’ strategy in implementing is through raise material and case example relevant to social life of students. The characteristics of digital natives adapted by teachers in Sociology essential material are digital literacy, multitasking, learning experience, collaboration, social, and purpose-oriented focusing not only on competency but also attitude and behavior in digitalization era. Overall, the adaptation of essential material in sociology subject exerts positive impact on motivation, competency, attitude, and behavior of students in utilizing digital technology and positioning themselves in social environment.